Polyculture of Genetically Improved Farmed Tilapia (GIF tilapia) and Penaeus vannamei Using Biofloc Technology – A Review - Joshna, M.; Ahilan, B.; Antony, Cheryl; Ravaneswaran, K.; Chidambaram, P.; Uma, A.; Ruby, P. (International Journal of Bio-resource and Stress Management, 2024)
According to Food and Agriculture Organization of the United Nations (FAO), aquaculture has grown faster and its expansion aimed at meeting the increase of world fish demand, and preserving natural fish stocks. Currently, to produce fish in quantity and quality requires reduction of the environmental impact from aquaculture, through the improvement of culture systems. Disease is the major factor affecting the development and expansion in aquaculture. Losses due to disease in shrimp farming are high. Various approaches to minimize the impact of disease on production are possible. Another approach to keep the pathogen pressure low is polyculture of shrimp and finfish. This practice makes shrimp farming more sustainable by reducing the environmental impact and the incidence of shrimp disease. Antimicrobial peptides in the fish skin kill shrimp pathogens, keeping pathogen pressure of bacteria and viruses low. In polyculture, shrimps can eat tilapia faeces and unused fish feed, while tilapia filter phytoplankton, reducing the risk of low dissolved oxygen levels at night. In addition, shrimp bioturbation at the pond bottom returns nutrients to the water column, enhancing phytoplankton production and consequently the natural feed available for the tilapia. Biofloc technology (BFT) is one of the most applicable and promising systems for sustainable aquaculture development. This technology is essentially based on the recycling of nutrients via microorganisms, primarily (i) heterotrophic bacteria, which convert nitrogen compounds into microbial biomass, in addition to serves as a source of food for aquatic organisms, and (ii) chemoautotrophic bacteria, which convert ammonia to nitrite and nitrate.